2006
DOI: 10.1111/j.1467-9450.2006.00491.x
|View full text |Cite
|
Sign up to set email alerts
|

Episodic chasing in pathological gamblers using the Iowa gambling task

Abstract: "Chasing ones losses" is a key symptom among pathological gamblers (PGs). This study focuses on quantitative differences in episodic chasing (i.e., sequences of disadvantageous decisions within a single gambling session) between PGs and non-pathological gamblers (NPGs). We compared 61 PGs and 39 NPGs on the Iowa Gambling Task (IGT) and the Zuckerman Sensation Seeking Scale (SSS). The PGs showed significantly more chasing and had significantly poorer decision-making strategies than NPGs, particularly among male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
71
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(82 citation statements)
references
References 32 publications
9
71
1
1
Order By: Relevance
“…As expected, a negative correlation between IGT scores and problem gambling severity was observed, indicating that the more severe the gambling involvement is, the more impaired decision making is, confirming previous studies (e.g., Brevers et al, 2012;Lakey et al, 2007). The decision making deficit found among pathological gamblers compared to healthy controls supports a large body of literature showing that problem gamblers have an insensitivity to future consequences and an inability to project themselves in the future (e.g., Ciccarelli, Griffiths, et al, 2016;Linnet et al, 2006). They appear unable to forego immediate and conspicuous rewards in order to obtain rewards that would be profitable in long-term, and making shortterm choices of questionable utility (e.g., Lorains et al, 2014;Petry, 2001;Wiehler & Peters, 2015).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…As expected, a negative correlation between IGT scores and problem gambling severity was observed, indicating that the more severe the gambling involvement is, the more impaired decision making is, confirming previous studies (e.g., Brevers et al, 2012;Lakey et al, 2007). The decision making deficit found among pathological gamblers compared to healthy controls supports a large body of literature showing that problem gamblers have an insensitivity to future consequences and an inability to project themselves in the future (e.g., Ciccarelli, Griffiths, et al, 2016;Linnet et al, 2006). They appear unable to forego immediate and conspicuous rewards in order to obtain rewards that would be profitable in long-term, and making shortterm choices of questionable utility (e.g., Lorains et al, 2014;Petry, 2001;Wiehler & Peters, 2015).…”
Section: Discussionsupporting
confidence: 79%
“…In fact, counter intuitively, many individuals with a gambling disorder are typically unable to cease the problematic behavior and are prone to chasing losses in an attempt to recover the money lost (Lesieur, 1979;Linnet, Røjskjaer, Nygaard, & Maher, 2006). Furthermore, it has been empirically demonstrated that problem gamblers show a foreshortened time horizon, since they are likely to consider the immediate consequences rather than the long-term outcomes (Ciccarelli, Malinconico, Griffiths, Nigro, & Cosenza, 2016;Nigro, Cosenza, Ciccarelli, & Joireman, 2016;Cosenza, Griffiths, Nigro, & Ciccarelli, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Over time, such a behavioral pattern will lead to losses against experienced poker players with better skill level. Uncorrected cognitive biases might lead to continued gambling despite losses, known as "chasing one's losses" (Dickerson, Hinchy, & Fabre, 1987;American Psychiatric Association, 1994;Linnet et al, 2006;O'Connor & Dickerson, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Pathological gambling is characterized by maladaptive gambling behavior (American Psychological Association, Diagnostic and Statistical Manual of Mental Disorders, 4th edition [DSM-IV], 1994), in which the individual continues gambling despite negative consequences such as incurred losses or jeopardized social relations. Cognitive biases, that is, distorted perceptions of probability and outcome, play a central role in problem gambling and are manifested in diverse ways, including overestimation or overconfidence of winning, selective attention toward gains, erroneous perceptions, superstitions, rituals, and illusion of control (Delfabbro, 2004;Delfabbro & Winefield, 2000;Floyd, Whelan, & Meyers, 2006;Goodie, 2003Goodie, , 2005Ladouceur, 2004a;Ladoucer, Tourigny, & Mayrand, 1986;Lakey, Goodie, & Campbell, 2006;Lakey, Goodie, Lance, Stinchfield, & Winters, 2007;Linnet, Rojskjaer, Nygaard, & Maher, 2006;Raylu & Oei, 2002;Toneatto, Blitz-Miller, Calderwood, Dragonetti, & Tsanos, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Problem gamblers are described as individuals who lose excessive amounts of money through gambling and exhibit patterns of gambling that compromise personal, family or vocational pursuits (Lesieur 1998). Features of problem gambling include gambling with increasing amounts of money to achieve desired outcomes (e.g., psychological rewards like excitement), chasing losses 22 , selling personal belongings or borrowing money to obtain funds to gamble, making larger 22 Chasing losses is an expression used to describe gambling behaviours where a gambling strategy is adopted, adhered to or increased despite gambling participation resulting in a series of or increasing losses of gambling wagers (Linnet et al 2006). Video lotteries are among the most popular and controversial gambling activities in Canada.…”
Section: Gambling and Health In Canadamentioning
confidence: 99%